Derivation of Newton's law of cooling and heating: Heating the water then cooling it down naturally to the room temperature - Wibowo, Edy; Ulya, Naily; Farizi, Mohammad Rakha; Fitriyanti, Nurwulan (Universitas PGRI Kanjuruhan Malang, 2023)
A simple experiment has been conducted to study Newton's law of cooling and heating by observing the nature of the increasing and decreasing water temperature by utilizing a data logger, a thermocouple, a pan, a hot plate, and water. The uncovered pan contained water which was subsequently heated on a hot plate. The water was heated at ambient temperature and normal atmospheric pressure to see that the temperature rose exponentially. Conversely, the temperature of hot water decreased exponentially when the heat source was switched off. The model for increasing and decreasing water temperature is following the Newton's law of cooling and heating. It was proven that the experimental data highly fit theoretical models. The temperature increment constant (ka) and the temperature decrement constant (kd) determined the rate of temperature changes. Low values of ka and kd led to the slow change in the temperature, either the increase or the decrease in the water temperature and vice versa. The ka > kd was observed for all given conditions so that the increasing rate in the water temperature was faster than its decrease. The result of this study can be applied as an example of contextual learning of physics for university students.